Characterizing the growth, morphology, productivity, and fruit quality of twenty-three strawberry cultivars in an indoor environment with sole source electric lighting - Lin, Yiyun; Kim, Changhyeon; Bassil, Nahla V.; Oliphant, James M.; Hardigan, Michael A.; Kubota, Chieri (Frontiers in Horticulture, 2025)
Indoor farming enables consistent production of superior-quality strawberries through optimized conditions. As strawberry growth, production, and quality can be largely affected by both genotype and environment, it is important to identify cultivars with traits desirable for indoor production. Twenty-three publicly available strawberry (Fragaria × ananassa) cultivars were selected from the USDA-ARS National Clonal Germplasm Repository as possible genetic resources for future breeding for indoor production and evaluated in a walk-in growth chamber with sole source electric lighting. Among strawberry cultivars examined, ‘Mara des Bois’ had desirable traits for indoor farming, including long-day photoperiodic response, early production, higher average weekly yield, and low sensitivity to dormancy-inducing photoperiod. Fruit quality traits, including size, calyx area, shape, color, total soluble solid content (Brix), titratable acidity (TA), and firmness were evaluated. ‘Chandler’ produced the largest fruit, ‘Sweet Sunrise’ showed the lowest calyx-to-fruit area ratio, and ‘Benton’, ‘Hood’, ‘Mara des Bois’, ‘NW 90054-37’, and ‘Puget Beauty’ fruit had a relatively high Brix-to-TA ratio. Correlations among productivity, quality, and morphological characteristics revealed the potential to enhance both productivity and quality by optimizing environmental conditions. The information on strawberry plant growth, development, and fruit production provided in this study can assist indoor growers in cultivar selection and potentially contribute to the development of new strawberry cultivars that thrive in indoor production environments.